MO426HANTA HEMORRHAGIC FEVER WITH RENAL SYNDROME CAUSED BY HANTAAN SEROTIPE IN BALKAN PENINSULA - AN UNESPECTED FINDING. (29th May 2021) - Lupusoru, Gabriela Elena; Ailincai, Ioana-Georgiana; Andronesi, Andreea Gabriella; Lupusoru, Mircea; Bernea, Lavinia Maria; Berechet, Andreea Ioana; Banu, Mihaela; Andronesi, Danut; Ismail, Gener
Abstract: Background and Aims: Hantavirus infection is a zoonosis rare in the Balkan Peninsula but with increasing frequency and geographic spread, causing two major syndromes, depending on the viral serotype: hemorrhagic fever with renal syndrome (HFRS) and cardiopulmonary syndrome (CPS). Because there is no specific treatment or vaccine for this condition, the key for minimizing the progression to chronic kidney disease, secondary hypertension or death is early diagnosis and prompt therapy. This paper presents a case of HFSR in which needle kidney biopsy played a major role in diagnosis and draws attention on this zoonosis that might be highly underdiagnosed in Balkan Peninsula. Method: A 26-year-old female with no medical history was admitted in our department with acute kidney injury (AKI), nephritic syndrome with nephrotic range proteinuria, high blood pressure, hepatic cytolysis, severe thrombocytopenia, anemia and leukocytosis, elevated LDH, normal haptoglobin, positive Coombs test (Table 1 ). Immunological testing (C3, C4, ANA, ANCA, antiGBM), viral infection markers (hepatitis B/C, HIV, Epstein-Barr, Cytomegalovirus), IgA/M/G were all negative and ADAMTS13 activity was normal. Abdominal sonography showed both kidneys of normal size and shape. A kidney biopsy was performed. The biopsy specimen showed macroscopic features of hemorrhage in the renal medulla. In immunofluorescence the staining was negative for IgA, IgG, IgM, C1q, C3c, k and λ chains, albumin and fibrinogen. Light microscopy (LM) revealed normal glomeruli and arterioles, dilated proximal tubules with resorption droplets at the apical pole and erythrocytes in the lumen, important interstitial hemorrhage in the medulla, with no inflammation or interstitial fibrosis. The electron microscopy (EM) showed segmental foot process effacement, endotheliosis of the peritubular capillaries, rare plasmocytes and macrophages in the interstitium (Figure 1 ). The aspect of hemorrhagic interstitial nephritis suggested Hantavirus infection. Serological testing revealed both IgM and IgG antibodies for the Hantaan serotype (HTNV). The final diagnosis was HTNV hemorrhagic interstitial nephritis with intrinsic AKI and secondary hypertension. MO426 Figure 1: A, B: LM, Toluidine Blue staining. Normal glomerulus. Resorption droplets in the proximal tubular cells. C, D: LM, Toluidine Blue staining . Extensive interstitial hemorrhage in medulla, tubulitis. E: EM . Interstitial extravasation of erythrocytes. F: EM. Endothelial swelling, foot process effacement. Results: The patient was treated with oral methylprednisolone 16mg/d for 2 weeks, with progressive tampering of the dose and removal after 2 months. She received antihypertensive and antiproteinuric treatment with ramipril. The evolution was good, with creatinine and liver enzymes returning to normal. Conclusion: HFRS belongs to a group of rare zoonoses in Balkan Peninsula, the most involved serotypes being Dobrava and Puumala. This case had positive serology for HTNV usually being found in China and Russia, but our patient didn't travel abroad before she got ill, so we can't consider the case as being an imported infection. That highlights a possible underdiagnosis of the disease in this region and also the need to re-evaluate geographic distribution of different strains and changes in ecological aspects given that they may pose a major risk to public health. The disease begins with flu-like symptoms and progresses to AKI with severe thrombocytopenia, anemia and coagulation disorders, being easily mistaken for haemolytic uremic syndrome. In a region with sporadic cases, we face diagnosis difficulties related especially to the absence of initial diagnosis suspicion, so we emphasize the need to include this pathology in the differential diagnosis algorithm of diseases evolving with thrombocytopenia, anemia, hepatic cytolysis and renal injury.